2008
DOI: 10.1029/2007jc004277
|View full text |Cite
|
Sign up to set email alerts
|

Energy dissipation of wind‐generated waves and whitecap coverage

Abstract: [1] The energy dissipation per unit area of the ocean surface attributed to fetch-or duration-limited wind-generated waves can be expressed in terms of wind speed, significant wave height and peak wave frequency. Such a parameterization equation can be exploited for obtaining a first order estimation of the rate of energy input through the air-sea interface in the world's oceans using satellite output of wind speed, wave height and wave period. For general wind wave events in the ocean with event duration long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 35 publications
6
65
0
Order By: Relevance
“…This threshold for spume production is significantly greater than the value of (0.013 to 0.038 Wm À2 ) for whitecap fraction found by Hwang and Sletten [2008]. This is consistent with observations that the wind speed threshold for whitecapping is lower than for spume droplet production.…”
Section: Analysis Of Breaking Surface Energy Fluxsupporting
confidence: 76%
“…This threshold for spume production is significantly greater than the value of (0.013 to 0.038 Wm À2 ) for whitecap fraction found by Hwang and Sletten [2008]. This is consistent with observations that the wind speed threshold for whitecapping is lower than for spume droplet production.…”
Section: Analysis Of Breaking Surface Energy Fluxsupporting
confidence: 76%
“…The whitecap coverage fraction obtained from such imagery routinely serves as a basis for parameterizations of a variety of air-sea exchange processes, including the turbulent dissipation rate in the upper ocean [5]. Additionally, visible imagery often reveals the tendency for surface foam and bubbles to congregate in long streaks or windrows.…”
Section: Visible Light Methodsmentioning
confidence: 99%
“…The net wave growth is controlled by the wind input and wave-breaking dissipation terms because the nonlinear waveÁwave interaction only causes energy exchange among wave spectral components. It has been shown that the net wave growth is one order of magnitude smaller than the wind input (Hasselmann et al, 1973;Resio, 1981;Hwang and Sletten, 2008). To the firstorder approximation, we scale F with R dis (R dis 0r w F), and eq.…”
Section: Turbulent Dissipation Rate In Wave-breaking Layermentioning
confidence: 99%
“…Attempts have been made to relate the breaking wave-energy dissipation rates to both wind and wave parameters (Guan et al, 2007;Hwang and Sletten, 2008;Kitaigorodskii, 2009). Zhao and Toba (2001), suggesting that the windÁsea Reynolds number R B is an effective parameter describing the breaking wave characteristics in terms of whitecap coverage.…”
Section: Turbulent Dissipation Rate In Wave-breaking Layermentioning
confidence: 99%